Islamic finances growth in Malaysia: the challenges / Azeman Abd Majid …[et al.] - Abd Majid, Azeman; Samsudin, Mawarti Ashik; Laton, Mohd Zahid; Abd Aziz, Nurul Nadia (2016)
Malaysia has recorded 17.3% growth of Islamic finances market between 2009 -2014 (MIFC, 2015a). It has tremendous potential to grow further in future. However, there are a few challenges that need to be resolved. This paper will discuss the challenges and issues that block the development of Islamic Finance in Malaysia and steps taken by the government to minimize the constraints. The understanding of challenges will alert the relevant parties and Government institution to prepare solutions and plans to minimize these challenges.